The effects of self-efficacy enhancement program for health volunteers on stroke surveillance and prevention - Suwintrakorn, Chiratchaya; Kalampakorn, Surintorn; Rawiworrakul, Tassanee (Thai Journal of Nursing, 2019)
The purpose of this quasi-experimental study was to investigate the effects of the volunteer self-efficacy promotion program on stroke surveillance and prevention. The experimental group received the volunteer self-efficacy promotion program through workshop and coaching during home visits. Data was collected by self-administered questionnaire and analyzed by using descriptive statistics, t-test and the repeated measures ANOVA. Results indicate that in the experimental group, knowledge of stroke, self-efficacy and surveillance and prevention of stroke after the experiment and follow-up period, had a significantly higher mean score than that before the experiment ( p <.05 ). When compared between groups it was found that the experimental group had a significantly higher mean score of knowledge of stroke, self-efficacy and surveillance and prevention of stroke after the experiment and 4 weeks follow-up than the comparison group ( p < .05 ).